Common Grounds: Thinking With Ruderal Plants About Other (Filmic) Histories - Teresa Castro (Philosophies, 2023)
This article explores the connections between film and ruderal plants: plants that grow spontaneously in anthropized environments and that we often call “weeds”. Thriving across damaged lands, ruderals are not only exceptional companions for thinking with at a time of ecological rupture, but also a way of engaging with less anthropocentric histories. As argued in this paper, such histories also pertain to film. Despite its timid representational interest in ruderals and “weeds”, cinema is concerned with the stories of collaborative survival, companionship and contaminated diversity raised by such turbulent creatures. Framed by a reflection on our ruderal condition, a discussion around some recent artists’ films allows us to explore some of these problems, while putting an accent on the idea of affective ecologies and involutionary modes of perception.